2015
DOI: 10.1016/j.dcn.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use in early adolescence: Evidence of amygdala hypersensitivity to signals of threat

Abstract: Cannabis use in adolescence may be characterized by differences in the neural basis of affective processing. In this study, we used an fMRI affective face processing task to compare a large group (n = 70) of 14-year olds with a history of cannabis use to a group (n = 70) of never-using controls matched on numerous characteristics including IQ, SES, alcohol and cigarette use. The task contained short movies displaying angry and neutral faces. Results indicated that cannabis users had greater reactivity in the b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 62 publications
2
38
1
Order By: Relevance
“…anterior cingulate cortex; right and left amygdala; right middle temporal gyrus) and no areas of decreased activation (Jager et al, 2010;Spechler et al, 2015), in line with our findings. In the two studies that investigated the effect of age of initiation of cannabis use which we were unable to include in our analyses, onset of use before the age of 16 was shown to be associated with a greater difference…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…anterior cingulate cortex; right and left amygdala; right middle temporal gyrus) and no areas of decreased activation (Jager et al, 2010;Spechler et al, 2015), in line with our findings. In the two studies that investigated the effect of age of initiation of cannabis use which we were unable to include in our analyses, onset of use before the age of 16 was shown to be associated with a greater difference…”
Section: Discussionsupporting
confidence: 92%
“…These results are to be considered in light of a number of limitations. We were unable to include a substantial number of identified studies as they had only reported the results of region of interest (ROI) analyses (Carey et al, 2015;Gruber et al, 2012;Harding et al, 2012;Hester et al, 2009;Jager et al, 2010;Jager et al, 2006;Jager et al, 2007;Pillay et al, 2008;Pillay et al, 2004;Roser et al, 2012;Sagar et al, 2015;Spechler et al, 2015;Zimmermann et al, 2017), focusing on areas relevant to the specific task used or of interest in light of previously hypothesized change in cannabis users. Of the results reported in these manuscripts, the two studies focusing on changes in adolescent cannabis users reported greater activation in cannabis users in task-related areas (left superior parietal cortex; inferior frontal gyrus; dorsolateral prefrontal cortex;…”
Section: Discussionmentioning
confidence: 99%
“…These findings are notable, however, as panic and anxiety symptoms are frequently reported side effects by naive and occasional cannabis users (Hall and Solowij, 1998). We also note fMRI evidence of hypersensitivity of the amygdala to signals of threat in a partly overlapping sample of cannabis using adolescents (Spechler et al, 2015) and a relationship between adolescent cannabis use and future mood complaints (Wittchen et al, 2007), even with comparatively low levels of use (Cheung et al, 2010).…”
Section: Discussionmentioning
confidence: 65%
“…Inappropriate developmental exposure to cannabinoid agents, on the other hand, can also disrupt the later expression of social behavior. Cannabis use in early adolescents was found to correlate with hypersensitivity to signals of threat (angry as compared to neutral faces) and higher levels of fMRI activity in the amygdala [74]. The persistence of the effect of developmental cannabinoid exposure into adulthood can be striking.…”
Section: Endocannabinoid Signaling In Social Impairmentmentioning
confidence: 99%